Schistosomiasis haematobia: histopathological course determined by cystoscopy in a patient in whom praziquantel treatment failed Esquistossomíase hematóbica: seguimento histopatológico determinado por cistoscopia em um paciente com falha terapêutica ao praziquantel - Iran Mendonça da Silva; Edson Pereira Filho; Roberto Thiengo; Paulo César Ribeiro; Maria José Conceição; Mônica Panasco; Henrique Leonel Lenzi (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
Schistosomiasis haematobia or urinary schistosomiasis is one of the main public health problems in Africa and the Middle East. A single dose of 40 mg praziquantel per kg body weight continues to be the treatment of choice for this infection. The aims of this follow-up were to study the post-treatment course of a patient infected with S. haematobium and not submitted to re-exposure, and to identify complications of the disease and/or therapeutic failure after praziquantel treatment by histopathological analysis. Treatments were repeated under medical supervision to ensure the correct use of the drug. In view of the suspicion of lesions in cystoscopy, the patient was submitted to bladder biopsy. The histopathological characteristics observed in biopsies obtained, after each treatment, indicated viability of parasite eggs and activity of granulomas. A Esquistossomíase Hematóbica ou Esquistossomíase Urinária é um dos principais problemas de Saúde Pública na África e no Oriente Médio. Uma única dose de praziquantel 40 mg/kg de peso, continua sendo o tratamento de escolha para esta infecção. Os objetivos deste seguimento foram: avaliar o período pós-tratamento de um paciente infectado com Schistosoma haematobium e não submetido à re-exposição e, identificar as complicações da doença e/ou falha terapêutica, após o tratamento com praziquantel, por análise histopatológica de material obtido por biópsia vesical. O tratamento foi repetido sob supervisão médica para assegurar o uso correto do medicamento. Na presença de lesões suspeitas a cistoscopia, o paciente foi submetido a biópsia vesical. As características histopatológicas observadas nos materiais obtidos por biópsia, após cada tratamento, indicaram viabilidade de ovos e atividade dos granulomas.